Acute respiratory distress syndrome: does histology matter? - Lorente, José A. (Crit Care, 2015)
Kao et al. have reported in Critical Care the histological findings of 101 patients with acute respiratory distress syndrome (ARDS) undergoing open lung biopsy. Diffuse alveolar damage (DAD), the histological hallmark of ARDS, was present in only 56.4 % of cases. The presence of DAD was associated with higher mortality. Evidence from this and other studies indicates that the clinical criteria for the diagnosis of ARDS identify DAD in only about half of the cases. On the contrary, there is evidence that the clinical course and outcome of ARDS differs in patients with DAD and in patients without DAD. The discovery of biomarkers for the physiological (increased alveolocapillary permeability) or histological (DAD) hallmarks of ARDS is thus of paramount importance.